Erythromelalgia mutation Q875E Stabilizes the activated state of sodium channel Nav1.7 - Stadler, Theresa; o' Reilly, Andrias; Lampert, Angelika (Journal of Biological Chemistry, 2015)
The human voltage-gated sodium channel Nav1.7 plays a crucial role in transmission of noxious stimuli. The inherited pain disorder erythromelalgia (IEM) has been linked to Nav1.7 gain-of-function mutations. Here we show that the IEM-associated Q875E mutation located on the pore module of Nav1.7 produces a large hyperpolarizing shift (-18 mV) in the voltage dependence of activation. Three-dimensional homology modeling indicates that the side chains of Gln-875 and the gating charge Arg-214 of the domain I voltage sensor are spatially close in the activated conformation of the channel. We verified this proximity by using an engineered disulfide bridge approach. The Q875E mutation introduces a negative charge that may modify the local electrical field experienced by the voltage sensor and, upon activation, interact directly via a salt bridge with the Arg-214 gating charge residue. Together these processes could promote transition to, and stabilization of, the domain I voltage sensor in the activated conformation and thus produce the observed gain of function. In support of this hypothesis, an increase in the extracellular concentration of Ca(2+) or Mg(2+) reverted the voltage dependence of activation of the IEM mutant to near WT values, suggesting a cation-mediated electrostatic screening of the proposed interaction between Q875E and Arg-214.
EVALuna2:2469